Study of the excitation of the isomeric state 7/2⁺ ⁸¹Sе nuclear in the reaction (γ,n) by the method of isomeric relationships - Mazur, V.M.; Bigan, Z.M.; Derechkei, P.S.; Pop, O.M. (Problems of Atomic Science and Technology, 2022)
Selenium is known for the transitional nature of the region from light to medium-heavy nuclei and their insufficient study. The ⁸²Se(γ, n) ⁸¹ᵐSe reaction yield was measured, and its cross-section in the range of gamma-ray energies 9…19 MeV was calculated. A comparison of the experimental results with theoretical calculations performed using the TALYS-1.9 software complex. The dominance of the statistical mechanism for this (γ, n) reaction was found. Селен відомий перехідним характером області від легких до середньоважких ядер і їх недостатньою вивченістю. Виміряно вихід реакції ⁸²Se(γ, n) ⁸¹ᵐSe та розраховано її переріз у діапазоні енергій гамма-випромінювання 9…19 МеВ. Проведено порівняння результатів експерименту з теоретичними розрахунками, виконаними за допомогою програмного комплексу TALYS-1.9. Було виявлено домінування статистичного механізму для цієї (γ, n)-реакції.